The Impact of the COVID-19 Pandemic on the Mental Health of Older Primary Care Patients and Their Family Members - Tara Seibert; Matthew W. Schroeder; Anthony J. Perkins; Seho Park; Eleanor Batista-Malat; Katharine J. Head; Tamilyn Bakas; Malaz Boustani; Nicole R. Fowler (Journal of Aging Research)
The COVID-19 pandemic introduced mandatory stay-at-home orders and concerns about contracting a virus that impacted the physical and mental health of much of the world’s population. This study compared the rates of depression and anxiety in a sample of older primary care patients (aged ≥65 years old) and their family members recruited for a clinical trial before and during the COVID-19 pandemic. Participants were dyads enrolled in the Caregiver Outcomes of Alzheimer’s Disease Screening (COADS) trial, which included 1,809 dyads of older primary care patients and one of their family members. Mean scores on the Patient Health Questionnaire-9 (PHQ-9) and the Generalized Anxiety Disorder Scale-7 (GAD-7) were measured and compared before and during the pandemic. We found no difference in depression and anxiety among dyads of older primary care patients and their family members recruited before and during COVID-19. Additionally, we found that older primary care patients and family members who reported their income as comfortable had significantly lower depression and anxiety compared to those who reported having not enough to make ends meet. Along with this, older primary care patients with a high school education or less were more likely to have anxiety compared to those with a postgraduate degree. Moreover, our findings support the notion that certain demographics of older primary care patients and family members are at a higher risk for depression and anxiety, indicating who should be targeted for psychological health interventions that can be adapted during COVID-19. Future research should continue monitoring older primary care patients and their family members through the remainder of the COVID-19 pandemic.